Synthesis, Characterization and Electrical Study of Ligand 5, 5'-(4H-1, 2, 4- triazole - 3, 5- diyl) bis (azaneylylidene)) bis (methaneylylidene)) bis (4,1-phenylene)) bis (methaneylylidene)) bis (azaneylylidene)) bis (4H-1, 2, 4- triazol- 3- amine with Some its Transition Metal ion Complexes - Amal H. Anatheil (Journal of Global Pharma Technology, 2019)
A new series of  some transition metal  ion (Cr  (III), Co (III), Fe (III) and Ni (II) complexes of new ligand {5, 5'- (4H-1, 2, 4-triazole- 3,5-diyl)bis(azaneylylidene))bis(methaneylylidene)) bis(4,1- phenylene)bis(methaneylylidene)) bis (azaneylylidene)) bis(4H-1,2,4-triazol-3-amine}(L) were  synthesized .A ligand was synthesized by reaction 2,5-di amino-1,2,4-triazole  and  two mole for Terephthalaldehyde in presence of ethanol and drops for acetic acid  to give 4,4'-((1Z,1Z')-((4H-1,2,4-Triazole-3,5,-diyl)bis(azaneylylidene))bis(methanelidene))dibenzaldehyde. Followed by reaction with two mole for 2, 5-diamino-1, 2, 4-triazole to give (L). The newly synthesized compounds were characterized by Fourier transform infrared (FTIR) Spectroscopy, Nuclear Magnetic Resonance Spectroscopy(1H NMR), elemental analyses (C, H, N), Mass Spectra data, magnetic susceptibility data, Molar electrical conductivity and atomic absorption. The Hyperchem 0.75 program have been used to draw the ligand geometry optimization and then study the electrostatic potential that given right data about the active site. It has been shown through all the above diagnostic measures that ligand is formed with the (Fe, Co and Cr) ions tetrahedral complexes and with the nickel formed square planer complex, Electrical insulation properties were studied for L and their complexes with (Fe, Co and Cr) , The measured electrical conductivity results are measured at room temperature with the applicable field frequency, Note when frequency increase the applied field of (50 Hz -1MHz) Connectivity increases due to the direct relationship between frequency and electrical conductivity. During the study, both ligands and their complexes were I2-doping showed that iodine increased the conductivity of Ligand, reduced the conductivity of complexes.Keyword: 1, 2, 4-Triazole, Terephthalaldehyde. Electrical conductivity, Doping, Magnetic susceptibility.